Observational study on carcinoma penis in Jharkhand - Alam, M. Afsar; Ranjan, Jitendra Kumar; Ahmed, Aftab; Mundu, M. (International Surgery Journal, 2019)
Background: Carcinoma of penis is relatively uncommon tumor. In India the incidence is relatively higher than western countries. It is the assumption that smegma is someway carcinogenic. Circumcision soon after birth confirm immunity against penile cancer. Many patients presents late either due to embarrassment or misdiagnosis. Surgery is the mainstay of treatment. Nodal involvement indicates a poor prognosis. Chemotherapy is relatively ineffective. Objective of the study to know the incidence, age group, avoidable risk factor and common presenting symptoms and 1st site of onset of growth of penile cancer in patients of Jharkhand. Methods: This is an observational study on carcinoma of penis in Jharkhand from 2012 to 2014. The patients were selected from the surgical outpatient and indoor patients, Department of General Surgery, RIMS, Ranchi, Jharkhand. The provisional diagnosis was based mainly on clinical examination and confirmed by biopsy. Results: Carcinoma of penis in Jharkhand commonly occurs in the 5th decade. This disease most commonly affects people of poor class with poor personal and sexual hygiene. The disease occurs commonly in uncircumcised Hindus particularly with phimosis and tobacco addiction appears to be a risk factor for penile cancer. Patients usually delay consultation with doctors until the disease is advanced. Conclusions: Penile cancer is associated with poor sexual hygiene, presence of phimosis and and consuming tobacco products is in important predisposing factor.